Protein‐Protein Interaction Mapping by 2C‐BioID. Issue 1 (27th August 2019) - Chojnowski, Alexandre; Werner, Hendrikje; Cook, Matthew; Sobota, Radoslaw M.; Burke, Brian; Stewart, Colin L.
Abstract: Protein‐protein interactions (PPIs) add an essential layer of complexity to the information encoded by the genome. Modulation of such interactions is a key feature of most, if not all, cellular activities and allows cells to respond rapidly to both internal and external signals and stimuli. In this respect, the development of the BioID assay to interrogate PPIs within a cellular context represents an important adjunct to the range of tools currently at researchers' disposal. To address some of its current limitations, we devised 2C‐BioID, in which biotin ligase and the protein of interest remain as separate entities until induced to associate. This is accomplished using the well‐established FKBP‐FRB dimerization system (based on the rapamycin‐induced binding of FK506 binding protein and FKBP12‐rapamycin binding domain.). The design of 2C‐BioID ensures that biotin ligase association with the protein of interest occurs only after addition of the rapamycin analogue AP21967. As such, 2C‐BioID alleviates potential targeting issues and improves the ability to exclude false positives, thereby refining the specificity of BioID‐generated interactomes. © 2019 by John Wiley & Sons, Inc.